CD40 Signaling Promotes CXCR5 Expression in B Cells via Noncanonical NF-κB Pathway Activation - Chuan Wei; Ying Chen; Lei Xu; Beibei Yu; Di Lu; Yanxiong Yu; Zhigang Lei; Rui Tang; Sha Zhou; Jifeng Zhu; Xiaojun Chen; Chuan Su (Journal of Immunology Research)
Chemokine receptor CXCR5-mediated control of B cell trafficking in the lymphoid tissues plays a central role in orchestrating the B cell function, which not only guides the colocalization of B cells with follicular helper T cells in the follicular mantle zone but also determines the position of germinal center dark and light zones. However, the mechanisms that regulate the expression of CXCR5 in B cells remain unclear. Here, we show that the expression level of CXCR5 in B cells was substantially reduced in vitro culture conditions, while being maintained in the presence of CD40 signals. Furthermore, CD40 signaling promotes CXCR5 expression in B cells at least partially through noncanonical NF-κB signaling pathway activation. However, other non-B cells also contributed to the optimal expression of CXCR5 in B cells through cell-cell contact and cytokine secretion. Our findings suggest that CD40 signaling-mediated activation of the noncanonical NF-κB pathway promotes the expression of CXCR5 in a B cell-intrinsic way to orchestrate the trafficking of B cells.